Formation and sedimentary filling of the Dnieper- Donets depression (geodynamics and facies) in the light of new data of paleotectonic modeling - Gonchar, V. V. (Geofizicheskiy Zhurnal, 2018)
Results of numerical modeling have been presented for development of the Dnieper-Donets depression based on the thermal problem for lithosphere with selecting the surface conditions of accumulation of the cover. A series of paleotectonic sections has been plotted with facial filling characterizing northwestern, central and southeastern parts of the depression. Modeling reproduces the initial transgressive and posterior regressive directionality of sedimentation during riftogenesis, iterative marine transgression in Tournaisian — Early Visean, step out to subcontinental conditions at the end of Middle Carboniferous; wide development is forecasted in southeastern part of DDD for abyssal depression formations of Late Devonian-Early Carboniferous. Frames of lithosphere and asthenosphere have been plotted; profiles of average temperature of anomalous mantle and tectonic component of plunge have been reconstructed. They certificate differences in the course of deep process during riftogenesis in different parts of the depression, for post-rift stage they give, on the contrary, the pattern of spatially steady descent.